P66 Testing for Trichomonas vaginalis (TV) by transcription mediated amplification (TMA). An evaluation in a large city clinic. (23rd May 2012) - Lawton, M; Schembri, G; Kingston, M
Abstract : Background: Trichomonas is worldwide, the commonest curable STI. While it's prevalence in the UK is less than other areas of the world, it remains a common cause of vaginal symptoms in women. Although not routinely tested in men it can be a cause of discharge and dysuria. It may be asymptomatic in both sexes. There is debate about the significance of TV infection, over and above it's symptomatology. The majority of centres use wet-film microscopy and/or culture for the detection of TV. The sensitivity of wet-film is recognised to be low. Culture has been considered the gold standard for TV detection, but is slow and costly. Methods: Symptomatic female patients and men with recurrent/persistent NSU were tested for TV using the same sample as the Chlamydia/gonorrhoea specimen. They were analysed using the Gen-Probe APTIMA TV assay in addition to the usual Chlamydia/gonorrhoea AC2 assay. Patients symptomatic of discharge had wet-film microscopy done as per standard clinical practice. Demographic data and symptomatology were recorded. Comparison was made between results from TMA and wet-film. Results: 1457 patients were tested for TV using TMA. Almost all (97%) were women. The overall prevalence for Trichomonas, Chlamydia and gonorrhoea via TMA was 3%, 8%, 1% respectively. TMA identified significantly more cases of TV compared to wet-film (41 vs 20, p=0.009). The prevalence of TV was significantly higher than gonorrhoea (p=0.002). Subset analysis will be done prior to presentation. Conclusion: Testing for TV via TMA identified significantly more infections compared with the current method of detection. It's overall prevalence was much higher than gonorrhoea which is routinely screened for in asymptomatic patients. Given the same sample is used for analysis, it does not add any additional clinic time or discomfort to the patient. Cost effectiveness of using TV TMA, particularly in asymptomatic patients has not yet been evaluated.